A Circular Approach for Making Fischer–Tropsch E-fuels and E-chemicals From Biogas Plants in Europe - Marchese, Marco; Gandiglio, Marta; Lanzini, Andrea (Frontiers in Energy Research, 2021)
In a mature circular economy model of carbon material, no fossil compound is extracted from the underground. Hence, the C1 molecule from non-fossil sources such as biogas, biomass, or carbon dioxide captured from the air represents the raw material to produce various value-added products through carbon capture and utilization routes. Accordingly, the present work investigates the utilization of the full potential of biogas and digestate waste streams derived from anaerobic digestion processes available at the European level to generate synthetic Fischer–Tropsch products focusing on the wax fraction. This study estimates a total amount of available carbon dioxide of 33.9 MtCO2/y from the two above-mentioned sources. Of this potential, 10.95 MtCO2/y is ready-to-use as separated CO2 from operating biogas-upgrading plants. Similarly, the total amount of ready-to-use wet digestate corresponds to 29.1 Mtdig/y. Moreover, the potential out-take of Fischer–Tropsch feedstock was evaluated based on process model results. Utilizing the full biogas plants’ carbon potential available in Europe, a total of 10.1 Mt/h of Fischer–Tropsch fuels and 3.86 Mt/h of Fischer–Tropsch waxes can be produced, covering up to 79% of the global wax demand. Utilizing only the streams derived from biomethane plants (installed in Europe), 136 ton/h of FT liquids and 48 ton/h of FT wax can be generated, corresponding to about 8% of the global wax demand. Finally, optimal locations for cost-effective Fischer–Tropsch wax production were also identified.